Principales determinantes de la rentabilidad de la Caja Municipal de Ahorro y Crédito de Huancayo periodo 2003 - 2015 - Alcorta Santisteban, Lucia Carolina (2016)
This research had as main objective to identify the main determinants of the profitability of Caja Municipal de Ahorro y Crédito de Huancayo. It is used a correlational descriptive methodology, in which the documentary analysis technique was applied as data collection instrument recording sheets was used. The sample was composed of financial statements and statistical information of Caja Huancayo during 2003-2015 published by the Superintendencia de Banca y Seguros and the Banco Central de Reserva del Perú, data processing was performed using the program E-views, an econometric model of ordinary least squares was run to find the quantitative relationship between variables. Among the main findings of the investigation, it is found that the main determinants of the profitability of Caja Huancayo during that period are, operational management, provisions concerning the expired credits, productivity per human force and economic growth due to the correct ratio of its parameters with the ROE; also worth mentioning that the operational management is the variable that affects greater proportion on the profitability of Caja Huancayo. Based on the results obtained and in contrast to the hypothesis, we note that the main determinants of Caja Municipal de Ahorro y Crédito de Huancayo during 20032015 are: operational management, provisions concerning the expired credits, productivity per human force and economic growth, this are the variables that significantly influence the ROE of Caja Huancayo.